PENGARUH KOMPENSASI, PENGEMBANGAN KARIR DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN - Purwanto S. Katidjan; Suharno Pawirosumarto; Albertus Isnaryadi (MIX: JURNAL ILMIAH MANAJEMEN, 2017)
Abstract. This study aims to determine and analyze the effects of compensation, careerdevelopment and communication on employee performance. This research usesquantitative method. The research population is all employees of PT. Metra Palma Fire(Medco Agro) Jakarta headquarter of 129 people. Sampling technique with AccidentalSampling, and the number of samples determined by Slovin formula, found 57respondents who were sampled. Data analysis using Multiple Linear Regression. Theresults showed that the compensation does not significantly affect employeeperformance, career development has no significant effect on employee performance,and communication has a significant effect on employee performance. While the testresults simultaneously indicate that compensation, career development, andcommunication have a significant effect on employee performance in PT. Metra PalmaFire (Medco Agro) Jakarta headquarters. Keywords: compensation, career development, communication, employee performance